Misunderstandings, mischaracterizations, and malicious accusations: A reply to Walby's (2021) SWAT Everywhere?. (September 2022) - Jenkins, Bryce; Semple, Tori; Bennell, Craig; Huey, Laura
To develop a more informed understanding of why tactical officers are used in Canada, we interviewed patrol and tactical officers from three Canadian police services (Jenkins et al., 2020). Interviewees indicated that tactical officers tend to be used on calls that go beyond the capabilities of patrol officers, including high-risk calls and calls unfolding in special environments, and that their use results in reduced threat to police and public safety. In response, Walby (2021) has argued that evidence-based policing (EBP) research of the sort we conducted is inherently biased. He also criticized our understanding of existing literature, took aim at our research methodology and conclusions, and questioned our academic integrity by claiming that we were paid by the participating police services to conduct the research. While Walby makes some valid criticisms of our research, his response is riddled with misunderstandings, mischaracterizations, and malicious (unfounded) accusations. After setting the record straight with respect to allegations regarding our nefarious motives to conduct the research, we argue that Walby completely misrepresents EBP research when he argues that it aims to support harmful police practices in exchange for financial support. We then correct numerous instances where Walby either mischaracterizes existing research or misrepresents our views (and those of our interviewees) when it comes to the use of tactical officers. We conclude by calling for more inclusive conversations to take place to address the issue of police militarization. These conversations must include community members, but they must also include the police.